Timing Irregularities and Glitches from the Pulsar Monitoring Campaign at Iar - Espinoza-Romo, C (EDP Sciences, 2024)
Context. Pulsars have a very stable rotation overall. However, sudden increases in their rotation frequency, known as glitches, perturb their evolution. While many observatories commonly detect large glitches, small glitches are harder to detect because of the lack of daily cadence observations over long periods of time (years). Aims. We aim to explore and characterise the timing behaviour of young pulsars on daily timescales, looking for small glitches and other irregularities, in order to further our comprehension of the real distribution of glitch sizes. Our findings have consequences for the theoretical modelling of the glitch mechanism. Methods. We observed six pulsars with up to daily cadence between December 2019 and January 2024 with the two antennas of the Argentine Institute of Radio Astronomy (IAR). We used standard pulsar timing tools to obtain the times of arrival of the pulses and to characterise the pulsar’s rotation. We developed an algorithm to look for small timing events in the data and calculate the changes in the frequency (ν) and its derivative (ν̇) at those epochs. Results. We find that the rotation of all pulsars in this dataset is affected by small step changes in ν and ν̇. Among them, we find three new glitches that have not been reported before: two glitches in PSR J1048−5832 with relative sizes of ∆ν/ν = 9.1(4) × 10−10 and ∆ν/ν = 4.5(1) × 10−9, and one glitch in the Vela pulsar with a size of ∆ν/ν = 2.0(2) × 10−10. We also report new decay terms on the 2021 Vela giant glitch, and on the 2022 giant glitches in PSR J0742−2822 and PSR J1740−3015, respectively. In addition, we find that the red noise contribution significantly diminished in PSR J0742−2822 after its giant glitch in 2022. Conclusions. Our results highlight the importance of high-cadence monitoring with an exhaustive analysis of the residuals to better characterise the distribution of glitch sizes and to deepen our understanding of the mechanisms behind glitches, red noise, and timing irregularities. © The Authors 2024.